(untitled) (Global Journal of Management and Business Research, 2018)
This study aimed to investigate the impact of Talent Management strategies on effectiveness Human Resources Information Systems in commercial banks working in Jordan, the Talent Management strategies represented by (attracting talents strategy, Developing talents strategy, Retention of talents strategy, and Succession strategy), and effectiveness Human Resources Information Systems. The study population consisted of all employees of commercial banks working in the capital of Jordan, a random simple sample was selected from the study population estimated (310) respondents. To achieve the objectives of the study, the descriptive analytical method was used through a questionnaire that used a major tool for data collection developed at the hands of elite researchers and writers in the field of the study variables. A number of statistical tools and methods were used such as Mean, Standard Deviation, one sample T-test, Multiple Regression, and Path analysis. The results showed that attracting talents strategy, Developing talents strategy, Retention of talents strategy, and Succession strategy, had a significant and positive effect on effectiveness Human Resources Information Systems in commercial banks working in Jordan, based on the study results, talent management strategies may be considered as critical success factors for effectiveness Human Resources Information Systems in commercial banks working in Jordan, the researcher recommends manager and decision makers to Offer an attractive career path for different groups of talents will also help to prevent putting people into the leadership path that actually do not want to be leaders or do not have the right competencies.